2021
DOI: 10.1111/eje.12662
|View full text |Cite
|
Sign up to set email alerts
|

Students’ learning environment perception and the transition to clinical training in dentistry

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 23 publications
4
17
0
2
Order By: Relevance
“…Durante el periodo 2018-2019, el Departamento de Odontología de la Universidad de Antofagasta desarrolló una modificación de su estructura curricular, en que de acuerdo a la planificación, desde el 3er semestre se inician las actividades de preclínico en modalidad de simulación, con la idea de mejorar el sistema de evaluación para valorar niveles cognitivos más altos al igual que sus habilidades psicomotoras antes de iniciar actividades clínicas, de la misma forma que los instrumentos de evaluación sean coherentes a una estructura basada en resultados de aprendizaje siguiendo el contexto del proceso de acreditación de la carrera. El uso de instrumentos que evalúan el ambiente educacional permite detectar posibles variaciones ante cambios o fases dentro de la estructura curricular, como las etapas de transición de asignaturas teóricas a pre-clínicas o de pre-clínicas a clínicas Serrano et al, (2021).…”
Section: Discussionunclassified
“…Durante el periodo 2018-2019, el Departamento de Odontología de la Universidad de Antofagasta desarrolló una modificación de su estructura curricular, en que de acuerdo a la planificación, desde el 3er semestre se inician las actividades de preclínico en modalidad de simulación, con la idea de mejorar el sistema de evaluación para valorar niveles cognitivos más altos al igual que sus habilidades psicomotoras antes de iniciar actividades clínicas, de la misma forma que los instrumentos de evaluación sean coherentes a una estructura basada en resultados de aprendizaje siguiendo el contexto del proceso de acreditación de la carrera. El uso de instrumentos que evalúan el ambiente educacional permite detectar posibles variaciones ante cambios o fases dentro de la estructura curricular, como las etapas de transición de asignaturas teóricas a pre-clínicas o de pre-clínicas a clínicas Serrano et al, (2021).…”
Section: Discussionunclassified
“…9 This is important because the nature of most operative procedures in dentistry is invasive and irreversible. 10 Accordingly, dental students' clinical simulation practice has always been an essential part of their training to develop the procedural and perceptual-motor skills, 11 to narrow the gap with the clinical phase of their education, 12,13 adding experience before the provision of direct patient care. 14 It would be unusual to allow a dental student to perform a clinical activity without having previously practiced it in a simulated environment.…”
Section: Introductionmentioning
confidence: 99%
“…All of the above pre-clinical training methods seek to narrow the "gap" between the transition from simulated cases to the treatment of real patients in which the students become responsible for patient care. However, it has been observed that this transition, at the beginning of students' clinical training, is a sensitive and stressful moment of their education, 12,13,21 which may affect their own competence confidence 22 and performance, 21 especially when confronted with patients' clinical uniqueness or anatomical diversity in irreversible treatments. 19 To date, little research has explored the impact on students' perceptions of simulated practice using both 3Dprinted and VR patient-specific models that reflect each patient's unique dentition.…”
Section: Introductionmentioning
confidence: 99%
“…These participating individuals will later showcase qualities of motivation, respect, and ethical decision making. 9,12,13 A thoughtful consideration to the students' perspective can also improve quality of life, educational experience, and positively influence future careers. 8 The "ideal" dental school environment may be defined as one that provides resources to students to help prepare them for their future professional careers.…”
Section: Introductionmentioning
confidence: 99%
“…An additional benefit to incorporating feedback is providing students with the opportunity to be engaged in their education. These participating individuals will later showcase qualities of motivation, respect, and ethical decision making 9,12,13 . A thoughtful consideration to the students’ perspective can also improve quality of life, educational experience, and positively influence future careers 8 …”
Section: Introductionmentioning
confidence: 99%